2015
DOI: 10.14569/ijacsa.2015.060819
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Hybrid Protection Architecture for Passive Optical Networks

Abstract: Abstract-Expanding size of passive optical networks (PONs) along with high availability expectation makes the reliability performance a crucial need. Most protection architectures utilize redundant network components to enhance network survivability, which is not economical. This paper proposes new self-healing protection architecture for passive optical networks (PONs), with a single ring topology and star-ring topology at feeder and distribution level respectively. The proposed architecture provides desirabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The basic ring-based PON is shown in Figure 3, which contains OLT module at the CO. In order to avoid the high deployment cost of OLT module, this architecture employs a single unit, owing to the fact that failure per year of OLT module is minuscule [4,18]. End-face of the OLT module is connected to a switching arrangement ðSA co Þ that extends the OF medium in both clockwise (CW) and counter clockwise (CCW) directions.…”
Section: Optical Fiber and Wireless Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic ring-based PON is shown in Figure 3, which contains OLT module at the CO. In order to avoid the high deployment cost of OLT module, this architecture employs a single unit, owing to the fact that failure per year of OLT module is minuscule [4,18]. End-face of the OLT module is connected to a switching arrangement ðSA co Þ that extends the OF medium in both clockwise (CW) and counter clockwise (CCW) directions.…”
Section: Optical Fiber and Wireless Communicationsmentioning
confidence: 99%
“…(6) shows that capacity of the network increases when more ONUs are placed per RN. Furthermore, it is observed that for P T ¼ 10 dBm, P edfa ¼ 25 dB, and R sen ¼À25 dBm, the ring-based hybrid protection architecture can efficiently support 128 subscribers simultaneously accessing the medium [18].…”
Section: Optical Fiber and Wireless Communicationsmentioning
confidence: 99%